2002
DOI: 10.1067/mge.2002.129603
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram monitoring facilitates sedation with propofol for routine ERCP: A randomized, controlled trial

Abstract: Electroencephalogram monitoring enables more effective titration of propofol dosage for sedation during endoscopy and is, therefore, associated with faster patient recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 0 publications
0
26
0
9
Order By: Relevance
“…It is unlikely that a truly independent and unbiased observer was recording the physiological outcomes, but this is also true for the large case series of NAPS and most randomized-controlled trials which compare NAPS to traditional sedation. [7][8][9][10][11][12][13][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] However, there is no reason to believe that the event reporting would be systematically different for MAC vs. GAP across the 69 CORI-NED sites. It should also be noted that the occurrence of CP complications might be suitably infrequent enough to be unable to detect some associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that a truly independent and unbiased observer was recording the physiological outcomes, but this is also true for the large case series of NAPS and most randomized-controlled trials which compare NAPS to traditional sedation. [7][8][9][10][11][12][13][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] However, there is no reason to believe that the event reporting would be systematically different for MAC vs. GAP across the 69 CORI-NED sites. It should also be noted that the occurrence of CP complications might be suitably infrequent enough to be unable to detect some associations.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recently, more than 140 000 cases of gastroenterologist or nurse-administered propofol sedation (NAPS) for endoscopic procedures have been published with no instances of significant adverse events (SAEs), such as endotracheal intubation or death reported. [7][8][9][10][11][12][13][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Despite the size of this experience, the comparative safety of propofol in the hands of gastroenterologists or anaesthesia personnel is unknown. Our objective was to determine the procedure-specific risk factors of cardiopulmonary (CP) events for propofol-based sedation for colonoscopy and upper endoscopy by utilizing the Clinical Outcomes Research Initiative National Database (CORI-NED).…”
Section: Introductionmentioning
confidence: 99%
“…A BIS value between 65 and 85 has been recommended for sedation. There have been studies reporting on BIS-guided titration of sedation for different procedures, including third molar extractions, endoscopy and interventional radiological procedures [11][12][13]. They showed that BIS-guided sedation was effective in reducing the dose of sedative medications and faster recovery.…”
Section: Discussionmentioning
confidence: 99%
“…The Practice Committee of American Society for Gastrointestinal Endoscopy has stated that the use of EEG monitoring may have a role in the future for the delivery of sedation during selected endoscopic procedures [13]. Wehrmann et al, [14], found that mean propofol dose was significantly lower in the group of patients sedated with EEG guided monitoring as compared with that of control group. The first and only technology approved by the U.S. Food and Drug Administration (1996), for marketing as an EEG based monitor of anaesthetic effect is the BiSpectral (BIS) analysis derivative [3].…”
Section: Study Design (Reg No: Ecr/215/inst/ker/2013)mentioning
confidence: 99%